Musculoskeletal injuries among Malaysian badminton players - Shariff, A.H.; George, J.; Ramlan, A.A. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
The majority of the injuries sustained by badminton players in this study were due to overuse, primarily in the knee. The majority of the injuries were diagnosed in younger players and occurred during training/practice sessions. There was no difference in terms of incidence and types of injuries between the genders.